Human-computer interaction -- INTERACT 2011 13th IFIP TC 13 international conference, Lisbon, Portugal, September 5-9, 2011, proceedings.Part IV - Campos, Pedro (Lecture notes in computer science, 2011)
The four-volume set LNCS 6946-6949 constitutes the refereed proceedings of the 13th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2011, held in Lisbon, Portugal, in September 2011. ((Text folgt)) The 47 papers included in the first volume are organized in topical sections on accessibility, affective HCI, computer-mediated communication, computer-supported cooperative work, evaluation, finding and retrieving, fun/aesthetic design, gestures, and HCI in the classroom.